Innovative Educational Technologies, Their Nature, Types And Theoretical Fundamentals (Texas Journal of Multidisciplinary Studies, 2022)
This article provides information on innovative educational technologies, educational innovations, their essence, types, theoretical foundations, the formation, development, improvement of the educational process, the application of pedagogical technologies and innovative approaches in the teaching process.